Issues on the Valuation of Tender Offers in the Philippines - Cayanan, Arthur S. (Philippine Management Review; Vol 30 (2023), 2023)
The announcements of tender offers have almost always raised several concerns, such as issues on undervaluation, non-availability of fairness opinion reports, and insufficient action on the part of the regulators. This paper discusses a number of such issues related to the valuation methods used in determining tender offer prices, especially those leading to the delisting of the shares. These issues may include the reasonableness of the assumptions used in the valuations. Aside from evaluating the different theoretical valuation models, this study also examines other concerns related to these tender offers such as the independence of the valuation entities. As a result, this study therefore presents suggestions towards addressing these aforementioned concerns that are being raised for regulators to consider.